1999
DOI: 10.1177/00912709922008272
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the Therapeutic Applications of Bisphosphonates

Abstract: The authors review the structural, pharmacologic, and clinical aspects of bisphosphonates, a class of drugs currently used to treat several disorders of bone and calcium metabolism. Pertinent literature on the bisphosphonates was reviewed with the help of a MEDLINE search and several bibliographies, including published clinical trials, monographs, and review articles. The bisphosphonates are analogs of pyrophosphate that, when given orally or intravenously, bind avidly to exposed bone mineral and disrupt bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 61 publications
0
14
0
2
Order By: Relevance
“…Many strategies, aimed to preserve bone stock and provide primary stability of implant, have been developed to inhibit the aseptic loosening and ensure the long-term survival [5]. Bisphosphonates (BPs), a family of pharmacological compounds with strong inhibitory effects on bone resorption for treating osteoporosis and other metabolic bone diseases, represents a potential candidate for modulating periprosthetic bone loss and osteolysis [6]. Compared with the first generation (G 1 ) of BPs, the second and the third generations (G 2-3 ) of BPs, including alendronate, risedronate, ibandronate, pamidronate, and zoledronic acid, have nitrogen-containing R 2 side chains and stronger therapeutic effect [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies, aimed to preserve bone stock and provide primary stability of implant, have been developed to inhibit the aseptic loosening and ensure the long-term survival [5]. Bisphosphonates (BPs), a family of pharmacological compounds with strong inhibitory effects on bone resorption for treating osteoporosis and other metabolic bone diseases, represents a potential candidate for modulating periprosthetic bone loss and osteolysis [6]. Compared with the first generation (G 1 ) of BPs, the second and the third generations (G 2-3 ) of BPs, including alendronate, risedronate, ibandronate, pamidronate, and zoledronic acid, have nitrogen-containing R 2 side chains and stronger therapeutic effect [6].…”
Section: Introductionmentioning
confidence: 99%
“…Aminobisphosphonates, pyrophosphate analogs which are in clinical use for the treatment and prevention of osteoporosis, Paget's disease, hypercalcemia caused by malignancy, and tumor metastasis in bone since they are potent inhibitors of bone resorption (5,42,43,45), were shown to inhibit the growth of amebas of the cellular slime mold Dictyostelium discoideum. It was found that the rankings of the aminobisphosphonate drugs in order of potency as inhibitors of Dictyostelium growth and as inhibitors of bone resorption are the same (46).…”
mentioning
confidence: 99%
“…This organelle would play the equivalent role of the bone mineral to which bisphosphonates are known to bind with high affinity (5,42,45); interestingly, D. discoideum has similar organelles, and it is possible that the accumulation of these drugs occurs through a similar mechanism (32,47,50). Moreover, interference of bisphosphonates with phosphate metabolism or other enzymes involved in intermediary metabolism in the Trypanosomatidae is plausible.…”
mentioning
confidence: 99%
“…They efficiently accumulate in bone due to their high affinity for calcium. Bisphosphonates are potent inhibitors of bone resorption used for the treatment of diseases characterized by excessive bone loss, such as Paget's disease, osteoporosis, and osteolytic tumor bone metastases (2)(3)(4). Bisphosphonates inhibit osteoclast activity at multiple levels; they prevent differentiation of macrophages into osteoclasts, block the activity of mature osteoclasts, and induce osteoclast apoptosis (5,6).…”
mentioning
confidence: 99%